Identifying and ranking new product factors of fashion industry (case study Iranian menswear brand) - Siamak Nazemi (TU Dresden; Faculty of Mechanical Science and Engineering;Chair of Development and Assembly of Textile Products, 2021)
In fashion industry, creative ideas and new products appear in new collections of brands presented in several ways, such as fashion week, exhibition etc. Iranian menswear also had the same strategy, but because of features of their customers, usually they use same designs and products in their new collections. Achieving new products in fashion industry can be related to design and technology aspect. Here we are looking for important factors affecting new products in Iranian menswear and also aiming at understanding which strategy are utilized in these product lines. Firstly this is done by gathering data from the Iranian Fashion association and 3 big Iranian menswear brands, secondly by interviews with experts from Iranian menswear brands, looking for answers of the study question. Twelve factors released from literature of study are divided in four sections: fabric sector, garment and accessories sector, and market sector. In 2010-decade, Iranian menswear brands focused on the technology factor in their new products, but during recent years, they changed their mind and now change direction to design departments. These phenomena happen due to the impact of social media on Iranian culture, with social media changing the behavior of the Iranian customer. Generally, accessing the directors of menswear brands was difficult, and during their interview they tried to hide some information. New products were an important factor in increasing market of any menswear brand. This study helps them to utilize the best strategy depending on their customers and market. This study confirms a new product’s impact on customer behavior and culture which could be difference with time.